CULTURAL VALUES IN POLICY PENETRATION: New Pattern of Communication in Creating Public Obedience - La Mani (DIA: Jurnal Administrasi Publik, 2020)
Many studies related to the policy of street vendors relocation in various cities in Indonesia, even in the world. However, there is still limited research examining the cultural variability of government and street vendors. Culture is not the only variable which can influence the behaviour of street vendors in responding the policies, but omnipresent cultural existence becomes a major factor in communication of government policies. The research was carried out in a qualitative explanatorywith the main focus on the implementation of street vendor policy relocation in Yogyakarta City, Indonesia. Data collection techniques were carried out through in-depth interviews with the actors or communicators in the communication of relocation policies to street vendors. The success or failure of the public policy implementation has many determinants. In a system perspective, a policy is in the frame of the environment which requires the integration of all elements which can influence it. This research has found that culture is the main determinant whichcan be one of the determinants of successful communication, creating compliance, forming positive opinions, conformity, and building consensus on the policy of street vendors relocation in Yogyakarta City, Indonesia.